The Politicization of Religion in Najib Kilani’s Zhillul Aswad: A Sociological Approach to Literature - Dhea Nazaliya (JPI: Jurnal Pustaka Indonesia, 2025)
This study examines the forms and implications of religious politicization in Najib Kilani’s novel Zhillul Aswad, a work set against the backdrop of Ethiopian history and politics. Using a qualitative descriptive approach, the study analyzes the narrative through a sociological lens, drawing on Swingewood’s sociology of literature to explore how religious rhetoric, institutions, and violence intersect in the text. The findings reveal that Kilani portrays religious politicization in multiple forms: manipulation of religious doctrine, the use of religion to justify violence, and the consolidation of political power through religious institutions. These forms are analyzed in relation to their social impacts, including the perpetuation of violence and the erosion of moral values. The study contributes to the literature on religious politicization by systematically categorizing the mechanisms of religious manipulation within the novel and offering a critical examination of how such politicization shapes societal and political dynamics. The implications of this research suggest that literature, as a reflection of social realities, plays a crucial role in critiquing the dangerous intersection of religion and politics, providing a valuable framework for understanding contemporary issues of religious exploitation and political control.